Odpowiedź :
1. 67 + x = 82 /- 67
x = 15
2. x + 38 = 76 /- 38
x = 38
3. 81 - x = 57 /- 81
- x = - 24 /:(-1)
x = 24
4. x - 43 = 38 /+ 43
x = 81
5. 68 + x = 94 /- 68
x = 26
6. x + 48 = 71 /- 48
x = 23
7. 83 - x = 39 /- 83
-x = - 44 /:(-1)
x = 44
8. x - 67 = 15 /+ 67
x = 82
Liczę na naj :)
Odpowiedź:
1. 67 + x = 82
x = 82 - 67
x = 15
2. x + 38 = 76
x = 76 - 38
x = 38
3. 81 - x = 57
- 1x = -24
x = 24
4. x - 43 = 38
x = 38 + 43
x = 81
5. 68 + x = 94
x = 94 - 68
x = 26
6. x + 48 = 71
x = 71 - 48
x = 23
7. 83 - x = 39
x = 39 - 83
x = -44
8. x - 67 = 15
x = 15 + 67
x = 82
Szczegółowe wyjaśnienie:
starałam sie dobrze zrobić